Exploring global calcimimetics research trends: a systematic and thematic review of Web of Science and Scopus databases from 1997 to 2024 - Abdelrahman, Riad; Musa, Taha H.; Mgbechidinma, Chiamaka Linda; Ahmed, Eltieb Omer (Frontiers in Nephrology, 2025)
BackgroundCalcimimetics are a group of medications that increase the sensitivity of the calcium receptors to extracellular calcium ions and inhibit the release of parathyroid hormone (PTH) in patients with chronic kidney disease (CKD).ObjectivesThe aim of this study was to analyze the global trends in the publication of articles on calcimimetics through bibliometric analysis of the Web of Science and Scopus databases, as well as to identify the most highly cited articles from 1997 to 2024.MethodsSystematic and thematic analyses were performed to provide substantial insights into calcimimetic research. Data were analyzed using VOS viewer (var1.6.6) and the Biblioshiny tool.ResultsA total of 3,500 documents were identified for analysis. There was an exponential growth in calcimimetic-associated publications (from 57 documents in 2004 to 258 in 2021). The mean of the total citations per article showed a decrease from 226 in 1998 to 0 in 2024. The United States was the most productive country. Goodman W. emerged as the most prolific author, with high-level metrics [n = 45, total number of citations (TNC) = 4,768, h_index = 27]. Fukazawa M. showed the longest research activity in the field, with 97 published documents in 25 years. Nephrology Dialysis Transplantation was the most published journal, with 112 documents and with an h_index of 43. The thematic KeyWords Plus analysis identified three key domains, including pharmacological targets (CaSR and cinacalcet) reported in niche themes and central CKD and mineral bone disorder (MBD) pathway (hemodialysis, vascular calcification, and vitamin D) case reports in emerging/declining themes. The small correlation between “diabetes” and “mineral metabolism” (despite shared CKD complications) suggests a critical research gap. While our thematic map highlighted robust research on the pathophysiology of CKD-MBD, critical clinical outcomes remain underexplored. Future trials should highlight these gaps, particularly in high-risk subgroups such as diabetic patients with CKD.ConclusionThe results of this review offer a summary of the global landscape, the key research areas, and possible future directions in calcimimetic research. This information can assist researchers in exploring the knowledge structure and understanding future trends in calcimimetic research, as well as in supporting collaboration toward advanced global research on calcimimetics.